CONTROLLING SENSITIVITY OF THE SENSOR WITH DIFFERENTIAL ELECTROSTATIC TRANSDUCERS - I. Z. Gilavdary; S. N. Mekid; N. N. Riznookaya (Приборы и методы измерений, 2015)
The problem of developing a sensor for measuring of moment forces of inertia and gravitation with minimal noise and minimal rigidity of the torsion suspension of proof mass (PM) is formulated. The possibility to solve this problem by a differential capacitive system, which simultaneously provides forming of the useful signal and reducing the torsion rigidity is shown. Sensor’s electromechanical circuit with differential electrostatic system is described. Method of calculating the electrostatic capacitance of the capacitor with an inclined plate is proposed. Calculations of electrical and mechanical forces moment acting on the movable plate of the differential capacitor in quasi-static mode are performed. It is shown that the main factor leading to the pull-in effect in the differential capacitor is the asymmetry of electrostatic system. The coefficient of asymmetry of the differential electrostatic system is introduced. The dependence on voltage of the resonance frequency of the sensor is received. The areas of the quasi-static stability of the system are calculated. It is shown that their boundaries are determined by the value of the coefficient of asymmetry, as well as by the value of the resonant frequency of the PM. It is shown that for reducing the resonant frequency of the sensor in more then ten times an unrealistically low values of the coefficient of asymmetry are required.